Focus on the Gut–Kidney Axis in Health and Disease - Stavropoulou, Elisavet; Kantartzi, Konstantia; Tsigalou, Christina; Konstantinidis, Theoharis; Romanidou, Gioulia; Voidarou, Chrysa; Bezirtzoglou, Eugenia (Frontiers in Medicine, 2021)
The recent new developments in technology with culture-independent techniques including genome sequencing methodologies shed light on the identification of microbiota bacterial species and their role in health and disease. Microbiome is actually reported as an important predictive tool for evaluating characteristic shifts in case of disease. Our present review states the development of different renal diseases and pathologies linked to the intestinal dysbiosis which impacts on host homeostasis. The gastrointestinal-kidney dialogue provides intriguing features in the pathogenesis of several renal diseases. Without any doubt, investigation of this interconnection consists one of the most cutting-edge areas of research with potential implications on our health.